Levels of isoforms of fibronectin and α5/CD49e integrin on lymphocytes and in blood plasma in the conditions of chronic diffuse liver diseases - H. V. Dolhikh; H. S. Maslak; V. I. Didenko; I. A. Klenina; А. О. Dolhikh (Regulatory Mechanisms in Biosystems, 2020)
Chronic diffuse liver diseases are characterized by accumulation of complex inflammatory infiltrate in the liver tissues, blood, and lympha, and activation of the immune system. Leukocytes become involved in the area of inflammation after the activation of receptors of blood adhesia, particularly integrins and their ligands. Plasma lymphocytes quickly activate the function of integrins by changing their conformation, leading to high affinity and underlying the formation of strong stable connection between the components of extracellular matrix. A vitally important role in the process of liver fibrogenesis is performed by a pro-fibrogenicic protein fibronectin which induces the expresson of collagen genes and precedes the deposition of other components of matrix. The studies were conducted in the group of patients suffering from chronic diffuse liver diseases of non-viral etiology aged 28–60 years, n = 36 and in the group of 15 practically healthy volunteer donors aged 25 to 52 years without a history of liver diseases using the methods of flow cytofluorometry, immunoenzymatic analysis, and quantitative real-time polymerase chain reaction. The patients of the group with chronic diffuse liver diseases were observed to have statistically significant decrease in the concentration of plasmatic form of fibronectin measuring 27.6% compared with the control group. We determined increase in the concentration of cellular fibronectin in blood plasma of patients with the diseases on average accounting for 63.8% compared with the norm, and the highest increase in this parameter equaling 77.2% was seen in patients suffering from drug-induced hepatitis. Significant increase in the level of exposure of cellular FN on blood lymphocytes was determined in patients with chronic diffuse liver diseases, measuring 231.8%, whereas the level of plasmatic form of fibronectin in these cells was decreased (statistically unreliable). For α5-integrin subunit, we determined a 390.8% increase in the level of its exposure in blood lymphocytes in the surveyed groups compared with the control. Level of blood lymphocytes that express the cellular fibronectin significantly decreased by 140.1%. Statistical characteristics of diagnostic possibility of the parameters of the level of plasmatic and cellular fibronectin in blood, determined over the analysis of ROC-curves, demonstrated excellent informativeness of these tests. Analysis of the possibility of predicting the presence of pathology using the model of logistic regression revealed zero error of prediction and maximum efficiency of the tests: intensity of exposure of α5-integrin receptor on the surface of lymphocytes, intensity of exposure of plasmatic fibronectin on the surface of lymphocytes, intensity of exposure of cellular fibronectin on the surface of lymphocytes, concentration of plasmatic fibronectin in blood, concentration of cellular fibronectin in blood plasma. These parameters may be proposed for further surveys for developing serologic biomarkers based on the parameters for diagnostics of chronic diffuse liver diseases.